Consequences of epigenetic derepression in facioscapulohumeral muscular dystrophy. Issue 6 (4th March 2020) - Greco, Anna; Goossens, Remko; van Engelen, Baziel; van der Maarel, Silvère M.
Abstract: Facioscapulohumeral muscular dystrophy (FSHD), a common hereditary myopathy, is caused either by the contraction of the D4Z4 macrosatellite repeat at the distal end of chromosome 4q to a size of 1 to 10 repeat units (FSHD1) or by mutations in D4Z4 chromatin modifiers such as Structural Maintenance of Chromosomes Hinge Domain Containing 1 (FSHD2). These two genotypes share a phenotype characterized by progressive and often asymmetric muscle weakening and atrophy, and common epigenetic alterations of the D4Z4 repeat. All together, these epigenetic changes converge the two genetic forms into one disease and explain the derepression of the DUX4 gene, which is otherwise kept epigenetically silent in skeletal muscle. DUX4 is consistently transcriptionally upregulated in FSHD1 and FSHD2 skeletal muscle cells where it is believed to exercise a toxic effect. Here we provide a review of the recent literature describing the progress in understanding the complex genetic and epigenetic architecture of FSHD, with a focus on one of the consequences that these epigenetic changes inflict, the DUX4‐induced immune deregulation cascade. Moreover, we review the latest therapeutic strategies, with particular attention to the potential of epigenetic correction of the FSHD locus. Abstract :